ANALISIS SISTEM DAN PROSEDUR BONGKAR MUAT KONTAINER PADA PT. (PERSERO) PELABUHAN INDONESIA II CABANG PONTIANAK - B51110025, Muhammad Farqi Faisal (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
PT (Persero) Pelabuhan Indonesia or abbreviated IPC is one of the state who is authorized to administer the business of the port as a provider of port services. To function properly, and to provide maximum service to service users, the IPC should be supported by a system and procedures are effective, efficient, and consistent and mutually hierarchical (berketerkaitan), between a system with other systems. The purpose of the thesis entitled "Systems and Procedures Unloading Containers on a PT (Persero) Pelabuhan Indonesia II Pontianak Branch" is to know and understand the application procedures of loading and unloading containers were instrumental in ensuring the smooth circulation of the flow of goods has been effective and to determine factor- what factors are causing delays in the implementation of the loading and unloading of containers in the field. The method used in this research is descriptive method in the form of case studies, the method of research that describes the state of the object in Pelindo II Pontianak branch. The results of research and discussion is on the organizational structure of PT. (Persero) Pelabuhan Indonesia II Pontianak Branch can be quite good to see that in this structure has been carried out the division of labor in accordance with the position / part held by each person, there is no duplicate work already done mutations to avoid job burnout and diversion the company's assets. Systems and procedures for loading and unloading containers at TPK Division Pelindo II Pontianak branch has not been carried out effectively and procedures have not been implemented optimally. In the implementation process of loading and unloading of containers on PT. (Persero) Pelabuhan Indonesia II Branch Pontianak experiencing barriers include: containers will be unloaded from the ship did not have space for placement in the yard, many supporting tools in Pelindo II branch Pontianak are often damaged due to age either tool the economic life and technical life is beyond the effective working period (old). In the flowchart procedure Unloading Planning and Implementation and Unloading Container Load Planning and Implementation of Container Load PT. (Persero) Pelabuhan Indonesia II Pontianak Branch has not menggambarkanbagan flow corresponding to the functions of the symbol that is supposed to show a flow of activities undertaken. The lack of supervision on the implementation of stevedoring services in the field the company makes it difficult to know the constraints that actually happening in the field. Â  Keyword: Loading and Unloading Systems and Procedures Containers